(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
Abstract The Purpose of the study was to investigate the effect of brand image benefit on customer satisfaction and Loyalty intention directly and indirectly based upon hypothetical model in the current study for a cosmetic brand (Fair lovely) at Gwalior (M.P) in India. The measures were reconstructed and re-standardized to make it suitable for the purpose of the study. Numbers of factors were identified through exploratory factor analysis for all the variables.Â The results of multiple regression revealed that there is a strong positive relationship between brand image and loyalty intention, While, the relationship between customer satisfaction and loyalty intention was found to be less weak. This indicates that there might be a mediation effect of customer satisfaction between brand image and loyalty intention. For evaluating the mediation effect Sobel test was applied and the result of the Sobel test was found to be positive. Hence, a mediating effect of customer satisfaction was found between Brand Image and Loyalty Intention. The measure of brand image was constituted of Functional, Social, Symbolic, experiential and appearance enhance. A survey was carried out on 200 respondents. The results also indicated that overall satisfaction does influence customers’ loyalty which implies that marketers should focus on brand image benefits to achieve customer loyalty.